Body mass index is related to autonomic nervous system activity as measured by heart rate variability: a replication using short term measurements - Koenig, Julian; Jarczok, Marc N.; Warth, Marco; Ellis, Robert J.; Bach, Claudia; Hillecke, Thomas; Thayer, Julian F. (The journal of nutrition, health & aging, 2014)
The present analysis is a replication of previous findings presenting first evidence of an association between body mass index (BMI) and autonomic nervous system (ANS) activity as measured by heart rate variability (HRV), in healthy non-obese adults.
Gesehen am 13.08.2020